ANALISIS KINERJA PLTU BARRU POMU UNIT 2: EVALUASI NET PLANT HEAT RATE DAN SPECIFIC FUEL CONSUMPTION PADA BERBAGAI VARIASI BEBAN - Hairun Apriadi Ramadhan S; Nasrun Nasrun (Universitas Wahid Hasyim, 2025)
This research aims to evaluate the performance of the Barru POMU Steam Power Plant (PLTU) Unit 2 through testing of Net Plant Heat Rate (NPHR), Specific Fuel Consumption (SFC), and Net Capability (Daya Mampu Netto - DMN). The tests were conducted at four variations of operating load, namely 75%, 85%, 92%, and 100%, using the input-output method and the heat loss method in accordance with the ASME PTC 4 standard. The test results show a Net Capability (DMN) of 44.64 MW. The lowest NPHR value was obtained at 100% load, which was 3,794.04 kcal/kWh with a Net SFC of 0.96 kg/kWh, while the highest NPHR was at 75% load, which was 4,166.23 kcal/kWh with a Net SFC of 1.02 kg/kWh. Boiler efficiency using the heat loss method ranged from 81.60% to 83.02%, increasing with the increase in load. The analysis indicates that operation at full load provides optimal efficiency with the lowest specific fuel consumption. This research provides baseline data for operational optimization and power purchase agreements in the context of PLN's generation consolidation into the Subholding Generation Company.